Informational Power and Perceived Collective Benefit Affecting the Users’ Preference for a Mobile Technology: Evidences From a Survey Study - Fantinelli, Stefania; Cortini, Michela (Frontiers in Psychology, 2018)
This study takes place from the idea that the personal usage of mobile technologies can bring positive outcomes to the user and to their society in an indirect way. Technologies studied in this work are defined as persuasive technologies (Fogg, 1997) because they are intentionally designed to modify the users’ attitude or behavior. This research is aimed to evaluate if the intention to use the application can be influenced by positive attitudes towards technology, by the persuasive power of the application and by the perceived fun. Participants (N=118; M=55; F=63; mean age=27.4; range age =15 to 69) filled in an online questionnaire that was partly based on the Media and Technology Usage and Attitude Scale (MTUAS – Rosen, Whaling, Carrier, Cheever, & Rokkun, 2013). An additional eight items were added to the scale, aimed at evaluating participants’ technophobia, technophilia, perceived technology pervasiveness and perceived persuasive power of technology. By using linear regression analisys, it was found that the application’s informational power and the perceived entertainment positively influenced the usage intention. Another interesting result, obtained through ANOVA, concerns a generational difference: baby boomers tended to trust more the fact that the single individual action through the application can have an effective impact on the environment. These results represent a basis for future in-depth investigations about socially relevant use of the ICT.